2021
DOI: 10.3390/ijms22168588
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Neurons and Glial Cells with Nanocolumnar TiN Films for Brain-Machine Interfaces

Abstract: Coupling of cells to biomaterials is a prerequisite for most biomedical applications; e.g., neuroelectrodes can only stimulate brain tissue in vivo if the electric signal is transferred to neurons attached to the electrodes’ surface. Besides, cell survival in vitro also depends on the interaction of cells with the underlying substrate materials; in vitro assays such as multielectrode arrays determine cellular behavior by electrical coupling to the adherent cells. In our study, we investigated the interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…While cells form protrusions and are more elongated on pristine TNSs, the cells exhibit a rounder morphology on TNSs implanted with higher C fluences. Interestingly, we found that the cell areas of both cell lines on TNSs are approximately one order of magnitude higher compared to cells on TiN and nanocolumnar TiN, as reported by Abend et al [ 85 ].…”
Section: Discussionsupporting
confidence: 86%
“…While cells form protrusions and are more elongated on pristine TNSs, the cells exhibit a rounder morphology on TNSs implanted with higher C fluences. Interestingly, we found that the cell areas of both cell lines on TNSs are approximately one order of magnitude higher compared to cells on TiN and nanocolumnar TiN, as reported by Abend et al [ 85 ].…”
Section: Discussionsupporting
confidence: 86%
“…Please also refer to previous studies by Abend et al for detailed material characterization. 39,41 In order to study possible influences of SH-SY5Y to U-87 MG cell ratios on cell behavior, cells were seeded as a coculture with different ratios of 80 : 20, 20 : 80, and 50 : 50 on…”
Section: Resultsmentioning
confidence: 99%
“…54 Cell morphology and adhesion studies of the employed cell lines on electrode materials ITO, TiN, and TiN nano are included in our previous study. 41 We expect the cell-surface adhesion and spreading behavior to be similar.…”
Section: Biomaterials Science Papermentioning
confidence: 95%
See 1 more Smart Citation